Clinical features of human immunodeficiency virus-associated malignancies in children and adolescents: a series of case reports - Grigory M. Sergienko; M. Yu. Goroshkova; E. P. Shabashkevich; D. V. Glushkov; N. V. Selivanova; M. M. Kotovich (Pediatric Hematology/Oncology and Immunopathology, 2026)
Introduction. Human immunodeficiency virus (HIV) infection in children is associated with an increased risk of malignant neoplasms, mainly lymphoproliferative, the development of which is linked to immunodeficiency, the duration of antiretroviral therapy, and coinfection with Epstein–Barr virus (EBV), the tumor may be the first manifestation of the disease. Materials and methods. A retrospective single-center study on children aged 0–18 years with HIV infection and morphologically confirmed malignancy. Results. Between 2011 and 2026, 5 patients with HIV infection and malignant neoplasms were identified. Lymphoproliferative disorders were the most common (4 out of 5); in one case, EBV-associated gastric adenocarcinoma was diagnosed. In most patients, tumors were detected at stages III and IV; in 2 cases, the diagnosis was made postmortem. During chemotherapy administered against the background of antiretroviral therapy, a complete response was achieved in one patient and a partial response in two; fatalities were due to disease progression and treatment complications against the background of severe immunodeficiency. Conclusion. The key factors influencing the prognosis of the disease are the CD4+ lymphocyte count, the timeliness of antiretroviral therapy initiation, and the presence of co-infections, primarily EBV.